An examination of the treatment of fees received by directors for South African tax purposes - Letlabe, Obed (University of the Witwatersrand, Johannesburg, 2023)
The study is about the way non-executive directors are treated for tax purpose by SARS and its reasoning regarding the VAT and PAYE liability of resident and non-resident non-executive directors. This research then evaluates both statutory and common law to determine whether non-executive directors can be treated as independent contractors. The report further evaluates whether the SARS reasoning is consistent with international conventions and treaties. The research suggests that it was never the legislature’s intention to treat services rendered by office holders as ‘enterprise’ liable for VAT
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Specialising in Taxation) to the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2023
Keywords: Non-executive directo; Non-resident non-executive director; Independent non-executive director; Statutory law; Independent contractor; Employee; Remuneration; Enterprise; Multiple or dominant impression test; PAYE; Constitution; UCTD; SDG-8: Decent work and economic growth